A survey of multicasting protocols for broadcast-and-select single-hop networks. - Hamad, A.M (IEEE Network : the magazine of global information exchange)
Multicast communication in single-hop broadcast-and-select wavelength-division multiplexing networks has received considerable attention from researchers. This article presents a comprehensive survey of the multicast scheduling techniques in this environment. It considers different challenges that are faced in the design of the multicasting techniques and presents a classification of such schemes. A survey of specific techniques is then presented and a comparison is drawn between such techniques